Development and assessment of feasibility of a ‘NeuroCare’ app for home care of neurosurgery patients - Nagi, Manisha; Kaur, Sukhpal; Kumar, Ashok; Singh, Amarjeet; Gandle, Chandershekhar; Thakur, Mukta; Aggarwal, Ashish; Chhabra, Rajesh; Gupta, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2024)
Background: Patients undergoing neurosurgery may require long-term care at home after discharge from the hospital. Mobile apps may assist their caregivers in care provision. This study aimed to develop and assess the feasibility of a ‘NeuroCare’ App for neurosurgery patients. Methods: The study was carried out at the neurosurgery department of a tertiary care institution. A mobile app was developed following a preliminary assessment of patients' post-surgery health problems and the caregivers' training needs. This bilingual app consisted of videos on oral care, back care, hand hygiene, Tracheostomy tube (TT) care, TT suction, TT change, RT feeding, etc. It was validated by 22 experts in nursing, public health, physiotherapy, and neurosurgery. The feasibility of the App was assessed on purposely selected 16 patients and their caregivers. Results: The majority (81.3%) of experts were highly satisfied with the functions of the app such as its contents, voice clarity, video clarity, content sequence, and understanding, and 80% of the caregivers preferred using the app in Hindi language. All the caregivers responded that the videos were not time-consuming. 60% of the caregivers were highly satisfied with the functions of the ‘Neuro-Care’ app. Conclusions: The ‘NeuroCare’ app was found to be feasible and may be a useful component for home care of postoperative neurosurgery patients.